2003
DOI: 10.2223/jped.962
|View full text |Cite
|
Sign up to set email alerts
|

Infantile colic incidence and associated risk factors: a cohort study

Abstract: Artigo submetido em 21.03.02, aceito em 22.01.03. ResumoObjetivos: estabelecer a incidência de cólica no lactente e seus determinantes.Métodos: entre maio e julho de 1999, a equipe de pesquisa visitou, diariamente, as três principais maternidades da cidade de Pelotas, RS, e todas as mulheres, após o parto, foram entrevistadas, e seus filhos acompanhados aos três meses. Definiu-se a criança com cólica conforme proposto por Wessel. Os possíveis fatores de risco avaliados foram: classe social, escolaridade matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 9 publications
0
28
1
11
Order By: Relevance
“…Surprisingly, this association has been evaluated in very few studies. Crowcroft et al published similar result but Lucassen et al and Saavedra et al reported contradicting finding [2,3,28] , the latter although benefited from a large sample size, was a retrospective study.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Surprisingly, this association has been evaluated in very few studies. Crowcroft et al published similar result but Lucassen et al and Saavedra et al reported contradicting finding [2,3,28] , the latter although benefited from a large sample size, was a retrospective study.…”
Section: Discussionmentioning
confidence: 87%
“…Among sur veys compared breast fed and for mula fed infants: four found no difference [17,18,26,27] , in three studies the occurrence rates among breast fed infants were slightly higher [2,28,29] , and in one it was slightly lower [22] . When analyzing the presence of association between breastfeeding and the development of colic, reverse causality is an important distorting factor, since the mother of crying children may stop breastfeeding because they relate the condition to feeding or believe that their milk is insufficient or weak.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, introducing teas into infant feeding has been identified as a risk factor for early weaning and for diarrhea occurrence, thus increasing morbidity and mortality risks (14) , which are negative effects the mothers do not seem to know about.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is based on the benefits of breastfeeding, such as protection against cramps in the first six months of life, as well as against respiratory and gastrointestinal infections, reducing the need for hospitalizations (2)(3)(4) . Breastfeeding satisfies an infant's nutritional needs, providing a better child development, especially in the first two years of life (5) .…”
Section: Introductionmentioning
confidence: 99%